2011
DOI: 10.1002/jcp.22495
|View full text |Cite
|
Sign up to set email alerts
|

NOS inhibition synchronizes calcium oscillations in human adipose tissue‐derived mesenchymal stem cells by increasing gap‐junctional coupling

Abstract: Adipose tissue-derived mesenchymal stem cells (ASCs) are a promising stem cell source for cell transplantation. We demonstrate that undifferentiated ASCs display robust oscillations of intracellular calcium [Ca(2+) ](i) which may be associated with stem cell maintenance since oscillations were absent in endothelial cell differentiation medium supplemented with FGF-2. [Ca(2+) ](i) oscillations were dependent on extracellular Ca(2+) and Ca(2+) release from intracellular stores since they were abolished in Ca(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…22 Fluorescence recovery was approximately 14% in control-treated thrombi but reduced to 2% in the presence of 37,43 Gap27, a connexin mimetic peptide (SRPTEKTIFII) designed to target the extracellular loops of Cx37 and Cx43, and the non-isotype selective connexin inhibitors, carbenoxolone (100μM) or 18β-GA (100μM) (Figure 2B). These observations are consistent with previous FRAP studies of gap junctions between adipose tissue-derived mesenchymal stem cells, 30 and provide strong evidence for the involvement of gap junction-mediated intercellular communication between platelets within a thrombus.…”
Section: Resultssupporting
confidence: 91%
“…22 Fluorescence recovery was approximately 14% in control-treated thrombi but reduced to 2% in the presence of 37,43 Gap27, a connexin mimetic peptide (SRPTEKTIFII) designed to target the extracellular loops of Cx37 and Cx43, and the non-isotype selective connexin inhibitors, carbenoxolone (100μM) or 18β-GA (100μM) (Figure 2B). These observations are consistent with previous FRAP studies of gap junctions between adipose tissue-derived mesenchymal stem cells, 30 and provide strong evidence for the involvement of gap junction-mediated intercellular communication between platelets within a thrombus.…”
Section: Resultssupporting
confidence: 91%
“…1C, D). This is consistent with data from human bone marrow-and adipose tissue-derived mesenchymal stem cells[38,39].Moreover, the decrease in Ca 2+ oscillation during AFMSC osteoblastic differentiation (Figs.1C, D) is in agreement with previous reports[34,40]. On the other hand, the observed increment in basal [Ca 2+ ]i is in line with the adipocyte differentiation program[41], as an increment in [Ca 2+ ]i upregulates the expression of PPARγ, a nuclear hormone receptor that acts as a critical transcriptional factor in adipocyte differentiation[42].…”
supporting
confidence: 89%
“…Our current observations indicate that NADPH oxidase complex is unlikely to be involved in the increase of ROS production induced by moderate electrical stimulation in primary rat skeletal muscle cells. However, in addition to the NADPH oxidase system, DPI can also inhibit the activities of mitochondria, nitric oxide synthase, and of a wide range of flavin‐containing enzymes such as xanthine oxidase, all of which are potential sites for ROS generation (Holland et al, 1973; Ragan and Bloxham, 1977; Rand and Li, 1993; Majander et al, 1994; Li and Trush, 1998; Galkin and Brandt, 2005; Sauer et al, 2011). The concentration of DPI used in the present study (2 µM) is five times lower than that typically reported by others, although we cannot fully guarantee that DPI inhibited the activity of NADPH oxidase only and a contribution of the NADPH oxidase for superoxide production induced by electrical stimulation cannot be fully ruled out.…”
Section: Discussionmentioning
confidence: 99%